The evolutionary diversity of locomotor innovation in rodents is not linked to proximal limb morphology - Hedrick, Brandon P. (Sci Rep, 2020)
Rodents are the most species-rich order within Mammalia and have evolved disparate morphologies to accommodate numerous locomotor niches, providing an excellent opportunity to understand how locomotor innovation can drive speciation. To evaluate the connection between the evolutionary success of rodents and the diversity of rodent locomotor ecologies, we used a large dataset of proximal limb CT scans from across Myomorpha and Geomyoidea to examine internal and external limb shape. Only fossorial rodents displayed a major reworking of their proximal limbs in either internal or external morphology, with other locomotor modes plotting within a generalist morphospace. Fossorial rodents were also the only locomotor mode to consistently show increased rates of humerus/femur morphological evolution. We propose that these rodent clades were successful at spreading into ecological niches due to high behavioral plasticity and small body sizes, allowing them to modify their locomotor mode without requiring major changes to their proximal limb morphology.